Youth participation in the Sago industry: A Malaysian case study - Ahmad Nizar, Yaakub; Hafizan, Mohamad Naim; Siti Zanariah, Ahmad Ishak; Awang Ideris, Awang Daud; Muhamad Faiz, Arshad (UKM Press, 2023)
Studies have shown that today’s youth are shunning away from agricultural activities leading to workforce shortages to sustain production. The present study includes a survey of 200 youths involved in the sago industry in Malaysia’s four major districts of Sarawak to understand their general perceptions of the sago industry and employment patterns in both sago and non-sago. Results showed that a proportion of the youth respondents were employed either full-time or part-time, with more than half working full-time in the private sector. Of great concern, about 25 per cent of them are not employed full-time. Nevertheless, approximately 70 or 35 per cent of the youth respondents admitted that they are engaged in part-time sago-related activities. Generally, rural youths have favourable attitudes toward the sago industry. The level of education is an essential factor influencing youths’ full-time employment in the sago industry. Whereas for part- time employment in the industry, age was a significant determinant.